2019
DOI: 10.1007/s11259-019-09746-y
|View full text |Cite
|
Sign up to set email alerts
|

Unique genetic features of canine adenovirus type 1 (CAdV-1) infecting red foxes (Vulpes vulpes) in northern Norway and arctic foxes (Vulpes lagopus) in Svalbard

Abstract: Canine adenovirus type 1 (CAdV-1) is the aetiological agent of infectious canine hepatitis (ICH) in domestic dogs (Canis familiaris). In spite of the widespread use of vaccination, CAdV-1 continues to circulate in the dog population. Although a high number of serological screenings have indicated that CAdV-1 is widespread in fox species, little is known about the potential role of foxes as reservoirs of CAdV-1. Furthermore, very little data exist on the molecular features of this virus in foxes. To add to exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Its prevention is a constant component in the vaccination schedule of puppies worldwide. CAdV‐1 causes encephalitis in foxes and was found to infect a number of other predators including wolf, coyote, jackal, otter, raccoon, and bear . A genomic variant, CAdV‐2, is associated with the so‐called kennel cough of dogs.…”
Section: Advs In Mammals (Mastadenovirus Atadenovirus)mentioning
confidence: 99%
“…Its prevention is a constant component in the vaccination schedule of puppies worldwide. CAdV‐1 causes encephalitis in foxes and was found to infect a number of other predators including wolf, coyote, jackal, otter, raccoon, and bear . A genomic variant, CAdV‐2, is associated with the so‐called kennel cough of dogs.…”
Section: Advs In Mammals (Mastadenovirus Atadenovirus)mentioning
confidence: 99%
“…The genus Mastadenovirus , within the family Adenoviridae , includes two types of Canine adenoviruses (CAdV), CAdV-1 and CAdV-2, which infect dogs and cause infectious canine hepatitis (ICH) and infectious tracheobronchitis, respectively. Apart from domestic dogs, several members of the Canidae [ 25 , 26 , 27 , 28 , 29 ], Ursidae [ 30 ], and Mustelidae families are susceptible to CAdV-1 and can even die from infection [ 31 ]. Although few studies on CAdV-1 infection in wild carnivores were carried out, it was frequently reported in association with encephalitis [ 27 , 28 , 32 ], including in wolves.…”
Section: Introductionmentioning
confidence: 99%
“…CAdV-1 and CAdV-2 are also widespread in wildlife. CAdV-1 primarily causes subclinical infection, but can be epizootic in wild carnivores belonging to the Canidae, Mustelidae and Ursidae families (Hechinger et al, 2017;Dowgier et al, 2018;Balboni et al, 2019). CAdV-1 has been reported in different fox species in several geographic areas (Thompson et al, 2010;Walker et al, 2016a,b).…”
Section: Introductionmentioning
confidence: 99%